Federal domestic assistance programs and state land policy development - Crosswhite, William M.; United States.; North Carolina. (State Planning Task Force, Dept. of Administration, 1970)
An initial survey of the land policy implications of federal domestic assistance programs.
HUD project no. N.C.P-112
"The preparation of this report was financed in part through a comprehensive planning grant from the Department of Housing and Urban Development."
"Public Agency Contract Number N.C.P.-112-2."
"May, 1970"--Abstract.
Includes bibliographical references and abstract.
Keywords: Regional planning. / fast / (OCoLC)fst01093120; Economic assistance, Domestic. / fast / (OCoLC)fst00901671; Economic assistance, Domestic / United States.; Regional planning / North Carolina.; United States. / fast / (OCoLC)fst01204155; North Carolina. / fast / (OCoLC)fst01204304